Ionic liquids with methotrexate moieties as a potential anticancer prodrug: Synthesis, characterization and solubility evaluation - Moshikur, R.M. (2019)
The technological utility of active pharmaceutical ingredients (APIs) is enormously improved when they are converted into ionic liquids (ILs). API-ILs possess better aqueous solubility and thermal stability than that of solid-state salt or crystalline drugs. However, many such API-ILs are not biocompatible or biodegradable. In the current study, we synthesized a series of IL-APIs using methotrexate (MTX), a potential anticancer prodrug, and biocompatible IL-forming cations (choline and amino acid esters). The MTX-IL moieties were characterized through 1 H NMR, FTIR, p-XRD, DSC and thermogravimetric analysis. The solubility of the MTX-ILs was evaluated in simulated body fluids (phosphate-buffered saline, simulated gastric, and simulated intestinal fluids). An assessment of the in vitro antitumor activity of the MTX-ILs in a mammalian cell line (HeLa cells) was used to evaluate their cytotoxicity. The MTX-ILs showed aqueous solubility at least 5000 times higher than that of free MTX and two orders of magnitude higher compared with that of a sodium salt of MTX in both water and simulated body fluids. Importantly, a proline ethyl ester MTX prodrug showed similar solubility as the MTX sodium salt but it provided improved in vitro antitumor activity. These results clearly suggest that the newly synthesized API-ILs represent promising potential drug formulations. Â© 2019 Elsevier B.V.